2009
DOI: 10.1007/s11547-009-0436-0
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasonography (CEUS) immediately after percutaneous ablation of hepatocellular carcinoma

Abstract: CEUS performed immediately after percutaneous ablation of hepatocellular carcinoma to evaluate treatment efficacy is compulsory in the case of RFTA but not for PEI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…However, there is still controversy over the role of CEUS vs CECT in the treatment response evaluation of HCC after ablation, which is probably influenced by the individual opinion and familiarity with the techniques [16] . Frieser et al [56] has concluded that CEUS is equal to CECT in evaluating treatment response; Gallotti et al [57] found that CEUS was excellent in evaluating treatment response after RFA, whereas it was inadequate for evaluating treatment response after EA.…”
Section: Ceus-guided Percutaneous Biopsy and Therapymentioning
confidence: 99%
“…However, there is still controversy over the role of CEUS vs CECT in the treatment response evaluation of HCC after ablation, which is probably influenced by the individual opinion and familiarity with the techniques [16] . Frieser et al [56] has concluded that CEUS is equal to CECT in evaluating treatment response; Gallotti et al [57] found that CEUS was excellent in evaluating treatment response after RFA, whereas it was inadequate for evaluating treatment response after EA.…”
Section: Ceus-guided Percutaneous Biopsy and Therapymentioning
confidence: 99%
“…Since April 1998, 34 studies [35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69] that consider different CEUS techniques have been published. Of these, 23 were on harmonic gray-scale CEUS [48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70], 12 were on Doppler CEUS modalities [36,37,38,39,40,41,42,43,44,45,46,47,48], one study compared both approaches [48] and another reported on carbon dioxide CEUS [35] Two studies have been excluded from our discussion due to the unavailability of papers [71,72].…”
Section: Assessing Treatment Responsementioning
confidence: 99%
“…Of these, 23 were on harmonic gray-scale CEUS [48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70], 12 were on Doppler CEUS modalities [36,37,38,39,40,41,42,43,44,45,46,47,48], one study compared both approaches [48] and another reported on carbon dioxide CEUS [35] Two studies have been excluded from our discussion due to the unavailability of papers [71,72]. …”
Section: Assessing Treatment Responsementioning
confidence: 99%
See 2 more Smart Citations